Constructing one-dimensional mesoporous carbon nanofibers loaded with NaTi2(PO4)3 nanodots as novel anodes for sodium energy storage. (February 2022) - Huang, Zan; Luo, Peifang; Wu, Qibao; Zheng, Honghong
Abstract: In this research, the novel one-dimensional mesoporous NaTi2 (PO4 )3 @C fibers (abbreviated as C-NTP-1D) are synthesized via an electrospinning method to promote the rate capability of pristine NaTi2 (PO4 )3 (NTP). The electrochemical properties, crystal structure and morphology for the resulted fibers have been explored by various electrochemical testing techniques, XRD, XPS, Raman spectroscopy, SEM as well as TEM. Benefiting from the designed mesoporous structure, the C-NTP-1D anode displays superior electrochemical properties. The specific capacities of 130.1 and 117.7 mAh g −1 is achieved at 0.1 and 2 C, and the C-NTP-1D presents the high capability of 89.1 mAh g −1 at 10 C following 500-cycle spans. Therefore, the designed mesoporous C-NTP-1D nanofibers can find potential applications as novel electrode for sodium-ion batteries. Highlights: The novel one-dimensional mesoporous NaTi2 (PO4 )3 @C fibers were fabricated via an electrospinning method. The one-dimensional carbon nanofibers were able to greatly promote the electrical conductivity of NaTi2 (PO4 )3 anode. The designed NaTi2 (PO4 )3 @C nanocomposite presented superior high-rate capabilities for sodium energy storage.